An Overview of Novel Agents for Cervical Cancer Treatment by Inducing Apoptosis: Emerging Drugs Ongoing Clinical Trials and Preclinical Studies - Liu, Lei; Wang, Min; Li, Xianping; Yin, Sheng; Wang, Bingqi (Frontiers in Medicine, 2021)
As the leading causes of cancer death, cervical cancer ranks fourth for both incidence and mortality. Although cervical cancer incidence and mortality rates have reportedly been in decline over last decades thanks to extensive screening and widespread of vaccination against human papilloma virus, platinum-based chemotherapy are still with no major outstanding improvements on survival of advanced cervical cancer. Thus, novel agents are urgently needed to improve therapy effect. And with the development of molecular biology and genomics, targeted therapy research has achieved a breakthrough development, in which anti-angiogenesis, immune checkpoint inhibitors and other treatments have been shown to be effective in the treatment of cervical cancer. Apoptosis is a crucial process for tumor progression. Drugs directed at inducing tumor-cell apoptosis are regarded as important treatment modalities. Besides, a number of novel compounds synthesized or derived from plants or microorganisms showed prominent anti-cancer activity by changing the apoptotic balance in cervical cancer. In this review, we summarized new target therapy drugs ongoing clinical trials treated for cervical cancer, and classified novel agents people focusing on to improve therapy effect pre-clinically. And in the end, we also discussed application prospects of new use of old drugs and drug combination, hoping to provide new ideas for researchers of cervical cancer treatment.